Histopathological study of meningioma in a tertiary care centre: a two years experience - Dr. Shalaka Khade; Dr. Ramesh Waghmare; Dr. Asha Shenoy (Tropical Journal of Pathology and Microbiology, 2019)
Background: Meningioma is a neoplasm arising from the arachnoidal cap cells in the meningeal coverings of the spinal cord and brain. These are the most common benign intracranial tumours and account for about 13-26% of all primary brain neoplasms. These are generally benign neoplasms, but about 10% are atypical or malignant. Objective: To study the variants and histopathological spectrum of meningioma. Material & Methods: This study includes 29 cases of meningioma diagnosed over a period of two years. Result: Most common variant was noted to be meningothelial meningioma followed by transitional meningioma. Out of the 29 cases, grade I were 96.55% whereas grade II were 3.44%. Conclusion: From our study, we conclude that meningothelial meningioma is the most common variant. Benign meningiomas are the most common type.